The N-terminal 33 amino acid domain of Siva-1 is sufficient for nuclear localization - Chen,J.Y. (2013)
Siva-1 induces apoptosis in multiple pathological processes and plays an important role in the suppression of tumor metastasis, protein degradation, and other functions. Although many studies have demonstrated that Siva-1 functions in the cytoplasm, a few have found that Siva-1 can relocate to the nucleus. In this study, we found that the first 33 amino acid residues of Siva-1 are required for its nuclear localization. Further study demonstrated that the green fluorescent protein can be imported into the nucleus after fusion with these 33 amino acid residues. Other Siva-1 regions and domains showed less effect on Siva-1 nuclear localization. By site-mutagenesis of all of these 33 amino acid residues, we found that mutants of the first 1-18 amino acids affected Siva-1 nuclear compartmentalization but could not complete this localization independently. In summary, we demonstrated that the N-terminal 33 amino acid residues were sufficient for Siva-1 nuclear localization, but the mechanism of this translocation needs additional investigation.